PRESERVASI SEBAGAI UPAYA UNTUK MENJAGA KELESTARIAN DAN MEMPERPANJANG USIA ARSIP STATIS KONVENSIONAL - Purnomo Purnomo (Perpustakaan Nasional RI, 2019)
Archiving or preservation is the process and work in order to physically protect archives against damage or elements of damage and to conduct restroration of damage archive part caused by both internal (intrinsic) factors of the archive itself and external factors. The archival preservation in intitutions is important for their long-term concerns because it can prevert more serve damage, loss of material and information.The purpose of archival preservation is to preserve their sustainability and to extend their life of use so that it can last longer and can be more useful. Therefore, there is an effort to convert files like the effort to digitize archives to keep them in electronic from to save space and to make the maintenance easy since there are many important archives that regrettably are in bad condition.